Not just by means alone: why the evolution of distribution shapes matters for understanding opinion dynamics. The case of the French reaction to the war in Ukraine - Richter, Friederike; Thiébaut, Cyrille; Safra, Lou (Frontiers in Political Science, 2024)
Understanding the dynamics of citizens' opinions, preferences, perceptions, and attitudes is pivotal in political science and essential for informed policymaking. Although highly sophisticated tools have been developed for analysing these dynamics through surveys, outside the field of polarisation, these analyses often focus on average responses, thereby missing important information embedded in other parameters of data distribution. Our study aims to fill this gap by illustrating how analysing the evolution of both the mean and the distribution shape of responses can offer complementary insights into opinion dynamics. Specifically, we explore this through the French public's perception of defence issues, both before and after the onset of the war in Ukraine. Our findings underscore how routinely combining classical approaches with the use of existing tools for measuring distribution shapes can provide valuable perspectives for researchers and policymakers alike, by highlighting the nuanced shifts in public opinion that traditional methods might overlook.